2013
DOI: 10.1371/journal.pone.0074235
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fat Mass and Obesity Associated (FTO) Protein Expression in Cardiomyocytes: Regulation by Leptin and Its Contribution to Leptin-Induced Hypertrophy

Abstract: The recently-identified fat mass and obesity-associated (FTO) protein is associated with various physiological functions including energy and body weight regulation. Ubiquitously expressed, FTO was identified in heart homogenates although its function is unknown. We studied whether FTO is specifically expressed within the cardiac myocyte and its potential role pertaining to the hypertrophic effect of the adipokine leptin. Most experiments were performed using cultured neonatal rat cardiomyocytes which showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…23 Both FTO and RPGRIP1L are located in one of the most important loci related to obesity. 5 Although FTO and RPGRIP1L functions in specific tissues are controversial, 24 some studies suggest that the expression of these genes regulates appetite by modulating leptin sensitivity at the hypothalamus: a decrease in their expression reduces the sensitivity to leptin, increasing appetite and food intake and contributing to an increase in body weight. 25 Our study found that hypermethylation in a CpG on CUX1 is associated with higher BMI, while the recent meta-analysis reported another CpG on CUX1 with an inverse effect on BMI.…”
Section: Discussionmentioning
confidence: 99%
“…23 Both FTO and RPGRIP1L are located in one of the most important loci related to obesity. 5 Although FTO and RPGRIP1L functions in specific tissues are controversial, 24 some studies suggest that the expression of these genes regulates appetite by modulating leptin sensitivity at the hypothalamus: a decrease in their expression reduces the sensitivity to leptin, increasing appetite and food intake and contributing to an increase in body weight. 25 Our study found that hypermethylation in a CpG on CUX1 is associated with higher BMI, while the recent meta-analysis reported another CpG on CUX1 with an inverse effect on BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several cardiac pathologies have shown increased cardiac fibrosis, with ECM expansion, myocyte hypertrophy, and apoptosis; examples include infarct and obesity with hyperleptinemia, where TRH hyperactivity has been observed (13,5). In these situations where the cardiac TRH system is upregulated, it appears that its inhibition may be protective for the heart.…”
Section: Discussionmentioning
confidence: 99%
“…FTO is ubiquitously expressed, with highest levels in brain and hypothalamus [ 1 , 2 , 11 ]. Although much attention has been devoted to FTO function in brain/hypothalamus [ 8 , 11 , 19 24 ], studies beyond the central nervous system are emerging [ 25 , 26 ]. Adipose tissue is the primary site for lipid storage, and acts as an endocrine organ regulating energy status via secreting and responding to hormones[ 27 ].…”
Section: Introductionmentioning
confidence: 99%